2011
DOI: 10.1159/000322649
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Advanced Emphysema with Emphysematous Lung Sealant (AeriSeal®)

Abstract: Background: This report summarizes initial tests of an emphysematous lung synthetic polymer sealant (ELS) designed to reduce lung volume in patients with advanced emphysema. Objectives: The primary study objective was to define a therapeutic strategy to optimize treatment safety and effectiveness. Methods: ELS therapy was administered bronchoscopically to 25 patients with heterogeneous emphysema in an open-label, noncontrolled study at 6 centers in Germany. Treatment was performed initially at 2–4 subsegments.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
98
1
3

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(104 citation statements)
references
References 40 publications
2
98
1
3
Order By: Relevance
“…Previous studies indicated that BioLVR achieved a reduction in lung volume. Six months after BioLVR, patients had significant improvement in their FEV 1 and scores on the SGRQ, and patients with advanced heterogeneous emphysema generally tolerated the procedure (74). Another study indicated that BioLVR improved lung function and quality of life for patients with homogeneous emphysema (75).…”
Section: Biolvrmentioning
confidence: 99%
“…Previous studies indicated that BioLVR achieved a reduction in lung volume. Six months after BioLVR, patients had significant improvement in their FEV 1 and scores on the SGRQ, and patients with advanced heterogeneous emphysema generally tolerated the procedure (74). Another study indicated that BioLVR improved lung function and quality of life for patients with homogeneous emphysema (75).…”
Section: Biolvrmentioning
confidence: 99%
“…20 ml of liquid foam sealant was injected over 10-20 s. Wedge position was maintained for 1 min following delivery to allow complete in situ polymerization. The scope was then repositioned at the next treatment site, and the procedure repeated until all treatments were completed [1]. The bronchoscopic images (Figure 3 a,b) showed that AeriSeal foam Sealant fills the targeted diseased alveolar region right and left upper lobe segment 1, where it is intended to induce atelectasis and to block collateral air flow.…”
Section: Case Reportmentioning
confidence: 99%
“…While these so-called Sealants have yielded overall good therapeutic results comparable to those of EBV, severe pneumonia and death were observed more frequently with this therapy. In addition, the majority of patients exhibited peri-interventional flu-like symptoms [32], and the time between the onset of effect and measureable therapeutic success took longer than EBV, requiring 6 -12 weeks [33]. In the meantime, the active substance AeriSeal (Aeris Therapeutics Inc., USA) is no longer commercially available.…”
mentioning
confidence: 99%